Creativity and innovation: a contribution of behavioral economics - Neto, J. C (2019)
Innovation in products and services is seen by scholars, by specialized media in management, and by some managers as the main currency in modern economies. This is because it allows high average market profits, fame for innovators, or brand growth, for example. However, in practice, most managers still treat innovation as a secondary issue on their agendas. This problem results from the inability of market professionals to analyze people inside and outside their companies. It is not possible to develop innovative products in a systematic way without treating this point effectively. Moreover, in this process, creativity is a necessary, but not necessarily sufficient, condition to be fulfilled and requires behavioral transformation. In this context, it is believed that behavioral economics can make a sufficient contribution in the form of an analytical marketing tool by offering an analysis closer to human beings' reality, and, thus, allow a better understanding of people's behavior in the process of innovation in the market.